SOME QUESTIONS OF FORMATION AND EVOLUTIONELECTORAL RIGHTS AND ITS PRINCIPLES (Journal of actual problems of jurisprudence, 2019)
Article is devoted politiko-legal evolution of the suffrage and its principles. Also are investigated historical ососбенностиformations of institute of elections.